2005
DOI: 10.1007/s00424-005-0027-4
|View full text |Cite
|
Sign up to set email alerts
|

Contralateral muscle fatigue in human quadriceps muscle: evidence for a centrally mediated fatigue response and cross-over effect

Abstract: The purpose of this investigation was to examine the effects of voluntary muscular fatigue in one lower limb and determine whether a 'cross-over' of fatigue is evident in the contralateral limb. Twenty-eight subjects (13 males and 15 females) performed a series of voluntary and evoked isometric contractions of both the dominant (exercised) and non-dominant (non-exercised) leg extensor muscles, prior to and after a fatigue protocol consisting of a 100-s sustained maximal isometric contraction (MVC) performed by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
73
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(90 citation statements)
references
References 32 publications
11
73
6
Order By: Relevance
“…However, the present findings are in opposition to several studies that have reported crossover fatigue effects (Rattey et al 2006;Martin and Rattey;Halperin et al 2014a, b;Kawamoto et al 2014). Rattey's et al (2006); Martin and Rattey (2007) and Halperin et al (2014a) used 100 s sustained MVICs of the dominant limb knee extensors to induce fatigue.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…However, the present findings are in opposition to several studies that have reported crossover fatigue effects (Rattey et al 2006;Martin and Rattey;Halperin et al 2014a, b;Kawamoto et al 2014). Rattey's et al (2006); Martin and Rattey (2007) and Halperin et al (2014a) used 100 s sustained MVICs of the dominant limb knee extensors to induce fatigue.…”
Section: Discussioncontrasting
confidence: 99%
“…Some research has shown that local fatigue occurring in one limb can result in decreased force production in the homologous muscle (Martin and Rattey 2007;Halperin et al 2014a;Kawamoto et al 2014) as well as in heteronymous muscles (Takahashi et al 2011;Kennedy et al 2013;Halperin et al 2014b) of a non-fatigued limb. This crossover or non-local fatigue effect has been identified for upper (Humphry et al 2004;Halperin et al 2014a, b) and lower limbs (Rattey et al 2006;Martin and Rattey 2007;McLean and Samorezov 2009;Paillard et al 2010;Halperin et al 2014a, b). Despite this evidence of crossover fatigue, controversy about its existence remains with many studies being unable to confirm its occurrence (Zijdewind et al 1998;Grabiner and Owings 1999;Todd et al 2003;Regueme et al 2007;Strang et al 2009;Place et al 2004;Ross et al 2007Ross et al , 2010Elmer et al 2013;Halperin et al 2014a, b).…”
Section: Introductionmentioning
confidence: 81%
See 3 more Smart Citations